Economic Empowerment Of The Community Through Optimizing The Understanding Of Financial Statements (MSMEs Bojongsoang Village Bandung) - Asri Suangga; Riyang Mardini; Rini Lestari; Rudy Hartanto; Annisa Nadiyah Rahmani; Boyke Rahmat Ramdani; Alia Alifa Ibrahim (Universitas Islam Bandung, 2022)
Financial recording and reporting training is expected to be able to overcome internal problems related to accountability that are often faced by MSMEs. The right assistance will help MSMEs to develop, from micro, small, to medium scale,can even be the forerunner of the emergence of large-scale industry. This research was conducted on MSMEs who are members of the